Evaluasi Kinerja dalam Pendidikan Islam - Sri Mulyani; Sunarto Sunarto (Reflection : Islamic Education Journal, 2025)
This article discusses the importance of performance evaluation in Islamic education, where the results of the evaluation serve as a reference to improve teaching methods, curriculum, and educational management to make them more relevant to students' needs and aligned with Islamic principles. The research method used in this article is library research. The data collection technique involves gathering documents such as books, journals, and other materials relevant to the topic. Furthermore, the data analysis technique employed in this study is descriptive analysis, where the data is analyzed through description.